Analisis Kebutuhan Sistem Informasi Untuk Menunjang Kegiatan Pencatatan Sipil - Widhi Gunawan; Mahfudz Ahnan Alfaruq; Echa Parhamda (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
Until now, the process of applying for and extending a Resident Identity Card (KTP) is still involved in bureaucratic procedures that take quite a long time. Apart from that, applications for Resident Identity Cards (KTP) still use paper which has the potential to be lost or damaged. When registering to make a Population Identification Card (KTP) at the Disdukcapil Office, there are often long queues which are exploited by irresponsible District Offices, who charge fraudulent fees on the grounds of speeding up the process of making a Resident Identification Card (KTP) or Family Card (KK).The system design method is based on work analysis (performance), information analysis, economic analysis, control analysis and efficiency analysis. Based on the results of research conducted, the Depok City Disdukcapil information system still has weaknesses in the form of no features for civil registration on the Depok population information and administration system (SIAK) website or its information so they still use third party applications. Information system and population information system website services (SIAK) Depok has a weakness in its service features, where on average most of the features cannot be used. Requirement analysis that has been carried out can help complete the website system in the Depok City Population Information and Administration System (SIAK), so that the civil registration process is fast, precise and accurate.